The dog that didn't bark: the case of Juan Carlos Rodríguez - Malcolm K. Read (Red de Universidades Lectoras, 2017)
The extensive body of research associated with the name of Juan Carlos Rodríguez has failed to receive the attention it deserves. The reasons commonly adduced, by way of explanation, focus upon factors external to the texts themselves. In this article I review two recently published books by Rodríguez and a celebratory volume with an eye to foregrounding other, internal barriers to Rodríguez's reception. These include a cyclical style of argumentation, of the kind associated with symptomal reading; the absence of a clear exposition of the Althusserian problematic upon which Rodríguez's seminal texts are otherwise based; and a critique of Althusser's alleged historicism, which, while it scores some useful points, was less than attentive to the philosopher's complexities. More damagingly, this same critique also fuelled the scurrilous distortions of Althusser's work still circulating throughout the bourgeois academy and so threatens Rodríguez's own work with premature closure.